2017
DOI: 10.26480/pjg.01.2017.24.26
|View full text |Cite
|
Sign up to set email alerts
|

Microfacies and Diagenetic Analysis of Lockhart Limestone, Shah Alla Ditta Area Islamabad, Pakistan

Abstract: The Larger Foraminifera made a major contribution to Paleocene and Eocene biota. The microfacies and diagenetic setting of the Paleocene Lockhart Formation were analyzed in Shah Alla Ditta area, Islamabad. The Lockhart Formation is highly fossiliferous, comprising of thin nodular limestone with interbedded shale/ marl. The lower contact is unconformable with Jurassic Samansuk formation while the upper contact is conformable with Margalla Hill Limestone. Rock samples were collected from the field and thin secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…According to Bilal and Khan (2017), the Lockhart Limestone, outcropped in Azad Kashmir, has experienced micritization, dolomitization, neomorphism, cementation, compaction and fracturing. In Islamabad, Khattak et al (2017) reported different diagenetic features in the Lockhart Limestone such as mechanical and chemical compaction, deep burial water pressure, pressure solution and tectonics-related fracturing. In the Kohat area, the diagenetic alterations of the Lockhart Limestone include tight packing, stylolitization, dolomitization, neomorphism (aragonite to calcite transformation) and sparfilled fractures (Fig.…”
Section: Diagenetic Fabric and Reservoir Quality Of The Lockhart Limestone: Petrographic Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Bilal and Khan (2017), the Lockhart Limestone, outcropped in Azad Kashmir, has experienced micritization, dolomitization, neomorphism, cementation, compaction and fracturing. In Islamabad, Khattak et al (2017) reported different diagenetic features in the Lockhart Limestone such as mechanical and chemical compaction, deep burial water pressure, pressure solution and tectonics-related fracturing. In the Kohat area, the diagenetic alterations of the Lockhart Limestone include tight packing, stylolitization, dolomitization, neomorphism (aragonite to calcite transformation) and sparfilled fractures (Fig.…”
Section: Diagenetic Fabric and Reservoir Quality Of The Lockhart Limestone: Petrographic Approachmentioning
confidence: 99%
“…In the Hazara and Kala-Chitta areas, the Lockhart Limestone is comprised of dark-colored nodular and massive limestone and intercalations of shale and marl (Shah 2009;Awais et al 2012 and. The Lockhart Limestone has been studied extensively by earlier investigators (e.g., Afzal et al 2005;Sameeni et al 2009;Yaseen et al 2011;Hanif et al 2013;Sameeni et al 2013;Ahmad et al 2014;Malik and Ahmed 2014;Khan et al 2016;Bilal and Khan 2017;Khattak et al 2017) in the context of sedimentology, biostratigraphy Fig. 1 Regional map showing location and tectonic setting of the Meyal Oil Field (marked by blue ellipse).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Lockhart Limestone was studied extensively by the geoscientists (Sameeni et al, 2009;Hasany and Saleem, 2012;Hanif et al, 2013;Ahmad et al, 2014;Ali et al, 2014;Nawaz et al, 2015;Khan et al, 2016;Saddique et al, 2016;Ahsan and Shah, 2017;Khattak et al, 2017;Khan et al, 2018;Siyar et al, 2018;Awais et al, 2019). According to Hasany and Saleem (2012), Lockhart Limestone is comprised of massive, argillaceous limestone in the Meyal Oil Field, Potwar sub-basin, Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopic observation on texture, composition (percentage of fragmented and/or non-fragmented shells, the percentage of micrite and terrigenous material, grain size composition), allochem type, diagenetic and microfossils content provide guidance on finding carbonate facies, index energy, sequence stratigraphy and depositional environment [9]- [11]. Field investigation and microscopic observation have been applied to facies and depositional interpretation of ancient carbonate several basins in Asia [8]- [10], [12], [13], including Indonesia [14].…”
Section: Introductionmentioning
confidence: 99%